Identification of Essential Amino Acids in the Bacterial α-Mannosyltransferase AceA - Abdian, Patricia Lorena (2000)
The alpha-mannosyltransferase AceA from Acetobacter xylinum belongs to the CaZY family 4 of retaining glycosyltransferases. We have identified a series of either highly conserved or invariant residues that are found in all family 4 enzymes as well as other retaining glycosyltransferases. These residues included Glu-287 and Glu-295, which comprise an EX(7)E motif and have been proposed to be involved in catalysis. Alanine replacements of each conserved residue were constructed by site-directed mutagenesis. The mannosyltransferase activity of each mutant was examined by both an in vitro transferase assay using recombinant mutant AceA expressed in Escherichia coli and by an in vivo rescue assay by expressing the mutant AceA in a Xanthomonas campestris gumH(-) strain. We found that only mutants K211A and E287A lost all detectable activity both in vitro and in vivo, whereas E295A retained residual activity in the more sensitive in vivo assay. H127A and S162A each retained reduced but significant activities both in vitro and in vivo. Secondary structure predictions of AceA and subsequent comparison with the crystal structures of the T4 beta-glucosyltransferase and MurG suggest that AceA Lys-211 and Glu-295 are involved in nucleotide sugar donor binding, leaving Glu-287 of the EX(7)E as a potential catalytic residue.